0807 NREM Parasomnias: Retrospective Analysis Of Treatment And Outcomes. (27th May 2020) - Limbekar, N; Pham, J; Yusuf, H; Budhiraja, R; Javaheri, S; Epstein, L J; Pavlova, M
Abstract: Introduction: NREM parasomnias are relatively common among children and sometimes persist in adulthood. These behaviors may result in injury or have negative impacts on functioning and quality of life thus necessitating treatment. The treatment is challenging given the lack of evidence for frequently used medications such as benzodiazepines (BDZ) or tricyclic antidepressants (TCA). The aim of this retrospective analysis is to determine the most frequently prescribed medications for treatment of NREM parasomnias and evaluate reported outcomes. Methods: We performed a retrospective chart review of all patients with NREM parasomnia diagnosed within BWH clinics examining the date of diagnosis, date of starting therapy, comorbidities, type of medication prescribed, and the reported change in symptoms or side effects at the individual's follow-up visits. Results: From 2012 to 2019, 123 patients (64 females, 59 male) at BWH clinics received the diagnosis of NREM parasomnia, including sleepwalking and night terrors. Mean age was 44. Comorbidities included depression=16, anxiety=32, seizures=6, RLS=9, epilepsy=5, insomnia=29, and OSA=57. Initial treatment included safety counseling (72), BDZ (7), TCA (4), and treatment of comorbidity (23). Treatment of OSA only (n=15) was effective in 66% (n=10) and 33% were lost to follow up. Of those with OSA treatment plus BDZ (n=6), treatment was effective in 50% (n=3). Of those receiving BDZ only (n=7), treatment was effective in 43%. Of those receiving Melatonin (8), treatment was effective among 62.5% (n=5). TCAS (n=4) were effective in 3 patients (75%). Treatment of comorbid conditions without pharmacotherapy (23) was effective in 35% (n=8) while the remaining 65% (n=15) were lost to follow up. Conclusion: Treating comorbid conditions such as OSA, insomnia, RLS, depression, and anxiety is a frequent treatment strategy. Additional pharmacologic treatment most commonly includes melatonin, BDZs, and TCAs. Support: None